Features of the education of children with speech impairments (Actual Problems of Psychology in Educational Institutions, 2018)
The article is devoted to the definition of the specifics of the organization in the initial stage of education of psychological and pedagogical support for children with speech disorders. The author outlined the essence of the problem of teaching primary school children with speech effects, systematized the forms of work, that promote the development of oral and written speech.
Keywords: junior school age; educational process; speech disabilities; communication skills; interactive profile